Italy : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This Financial System Stability Assessment report provides a review of .Italian financial system. The announcement of outright monetary transactions (OMT) and steps toward a banking union have blunted the impact of the sovereign debt crisis on banks, and the expansion of European Central Bank (ECB) liquidity facilities has temporarily shielded Italian banks from wholesale funding volatility. Stress tests suggest that the system as a whole is able to withstand both the already weak baseline macro outlook and the phase-in of Basel III requirements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet